Protective effect of cysteinyl leukotriene receptor antagonist montelukast in bleomycin-induced pulmonary fibrosis - CEYHAN, BERRİN; ÇELİKEL, ÇİĞDEM; BOZKURTLAR, EMİNE; ŞENER, GÖKSEL; OLGUN YILDIZELİ, ŞEHNAZ; LAÇİN, TUNÇ (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2018)
Background: This study aims to investigate the early- and late-term effects of pharmacological inhibition of cysteinyl leukotriene activity by using montelukast in bleomycin-induced inflammatory and oxidative lung injury in an animal model. Methods: The study included 48 male Wistar albino rats (weighing 250 g to 300 g). Rats were administered intratracheal bleomycin or saline and assigned into groups to receive montelukast or saline. Bronchoalveolar lavage fluid and lung tissue samples were collected four and 15 days after bleomycin administration. Results: Bleomycin resulted in significant increases in tumor necrosis factor-alpha levels (4.0 +/- 1.4 pg/mL in controls vs. 44.1 +/- 14.5 pg/mL in early-term vs. 30.3 +/- 5.7 pg/mL in late-term, p<0.001 and p<0.001, respectively), transforming growth factor beta 1 levels (28.6 +/- 6.6 pg/mL vs. 82.3 +/- 14.1 pg/mL in early-term vs. 60.1 +/- 2.9 pg/mL in late-term, p<0.001 and p<0.001, respectively), and fibrosis score (1.85 +/- 0.89 in early-term vs. 5.60 +/- 1.14 in late-term, p<0.001 and p<0.01, respectively). In bleomycin exposed rats, collagen content increased only in the late-term (15.3 +/- 3.0 mu g/mg in controls vs. 29.6 +/- 9.1 mu g/mg in late-term, p<0.001). Montelukast treatment reversed all these biochemical indices as well as histopathological alterations induced by bleomycin. Conclusion: Montelukast attenuates bleomycin-induced inflammatory and oxidative lung injury and prevents lung collagen deposition and fibrotic response. Thus, cysteinyl leukotriene receptor antagonists might be regarded as new therapeutic agents for idiopathic pulmonary fibrosis.
Keywords: Bleomycin; collagen; glutathione; interstitial lung disease; malondialdehyde; myeloperoxidase; transforming growth factor beta 1; tumor necrosis factor-alpha; GROWTH-FACTOR-BETA; NECROSIS-FACTOR-ALPHA; MOUSE MODEL; MECHANISMS; PATHOGENESIS; COLLAGEN; INJURY; CELLS; PROLIFERATION; EXPRESSION